Influence of promotions, price perceptions, service quality towards customer loyalty through customer satisfaction Gojek in Jakarta - Vemberain, Jesselin; Rakhman, Abdullah (Jurnal Ekonomi Perusahaan, 2024)
The evolution of technology has deeply impacted various industries, notably transportation services, facilitated by advancements like online platforms such as Gojek in Indonesia. In this research, the authors expect the direct and positive influence of promotion, price perception, and service quality on customer satisfaction and the indirect impact on customer loyalty. Questionnaires were distributed to 198 Gojek users in Jakarta. The data analysis using SPSS and WarpPLS suggests strong correlations between promotion, price perception, service quality, customer satisfaction, and customer loyalty. However, while promotion and price perception significantly affect customer loyalty, the impact on service quality is negligible. Customer Satisfaction acts as a mediator between these variables and customer loyalty. Further research can utilize additional variables because the independent variables used in this study can only explain 60% of the purchasing decision process. Other variables explain 40 % of it.